Estimation of Stature from the Length of the Sternum in the Ethnic Meitei Population– A Study in Medicolegal Autopsies - Zohlupuii , L B; Devi , T M; Haricharan , A; Memchoubi , P H (Journal of Indian Academy of Forensic Medicine, 2023)
Identification is necessary for living persons, dead persons, decomposed bodies, and mutilated and burnt bodies. In some cases where long bones are not available; the fresh sternal length can be used for stature estimation. Forty male cases belonging to the ethnic Meitei population within the age group 14-70 years were studied. Linear regression analysis was applied for the different sternal lengths to derive regression equations for the estimation of the stature of the study population. The linear regression obtained for the length of the manubrium, length of the body, combined length of the manubrium and the body and the total sternal lengths were Y=5.7641X +138.53, 1 Y=2.277X +140.6, Y=2.3229X +128.81 and Y=2.4786X +116.05 respectively. The maximum correlation was observed for the total 2 3 4 sternal length (R=0.569) followed by manubrium (R=0.475), the combined length of manubrium and mesosternum (R=0.462) and mesosternum (0.374). The study showed that there was a moderate positive correlation between all the sternal measurements with the cadaveric length.